Phenomenological Typology of Entrepreneurship and Self-Employment of Working Graduated Women in Tehran - mehrnoush Foroutan; khadijeh safiri; Tahereh Mirsardo (توسعه اجتماعی, 2021)
The present study is a phenomenological effort for the typology of entrepreneurship and self-employment of working graduated women in Tehran, which has been done with phenomenological approach and in-depth and semi-structured interview tools, with the participation of 50 women entrepreneurs, self-employed and experts in this field. Therefore, after receiving a conceptual and practical definition of entrepreneurship and self-employment from the perspective of participants and trying to understand their attitude towards entrepreneurship indicators, efforts were made to obtain possible classifications based on differential characteristics. The results indicate that from the participants' point of view, in a society with a traditional culture, self-employed women are considered entrepreneurs due to innovation in "employment role stereotypes". Entrepreneurs are also categorized according to various categories, which 1- in terms of the opportunity conditions falls into the categories of "opportunity finding, opportunity building and conversion", 2- in terms of the field of employment falls into "industry , Trade and services”, 3- in terms of field of activity falls into" scientific, cultural, economic and social ", 4- in terms of entrepreneurship type falls into", educational-research, social-ethical, motivational-supportive, intermediary-transitional, economic-productive, multidimensional-developmental", 5- in terms of  motivation and purpose, they were divided into "self-centered, Other axis/heterogeneous, interactive/ Bilateral, general-oriented", and finally 6- in terms of entrepreneurial result falls into "self-employed and job-creating" categories.